2015
DOI: 10.1007/s12665-015-4674-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of groundwater recharge and its relation to land degradation: case study of a semi-arid river basin in Iran

Abstract: Groundwater extraction is one of the most important criteria of land degradation especially land subsidence in arid and semi-arid areas. Understanding the relationship between water extraction and recharge of groundwater can lead to better watershed management. For the estimation of groundwater recharge in Razan-Ghahavand watershed in Central Iran the Soil and Water Assessment Tools was used. Model calibration was done by using SUFI-2 based on monthly river discharge and annual crop yield, where crop yield was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…SWAT is a semi-distributed model which is most commonly applied to simulate water fluxes on the catchment scale with diverse agricultural management options and under various hydrologic conditions over long periods of time (Arnold et al, 2012). As a process-based hydrological model, SWAT has proven its capability for climate change impact studies (Emami and Koch, 2019;Tigabu et al, 2021). The SWAT model of the Halilrood Basin is divided into 285 sub-basins and 6091 hydrologic response units (HRUs), defined by land use (FAO, 2009), slope, and soil type (ESA, 2010).…”
Section: Hydrological Modelmentioning
confidence: 99%
“…SWAT is a semi-distributed model which is most commonly applied to simulate water fluxes on the catchment scale with diverse agricultural management options and under various hydrologic conditions over long periods of time (Arnold et al, 2012). As a process-based hydrological model, SWAT has proven its capability for climate change impact studies (Emami and Koch, 2019;Tigabu et al, 2021). The SWAT model of the Halilrood Basin is divided into 285 sub-basins and 6091 hydrologic response units (HRUs), defined by land use (FAO, 2009), slope, and soil type (ESA, 2010).…”
Section: Hydrological Modelmentioning
confidence: 99%
“…The water in each HRU can be stored in four levels: snow, soil profile (0-2 m), shallow aquifer (0-2 m) and deep aquifer (2-20 m). Rafiei Emam et al [15] revealed that a single HRU could not show the characteristics of a sub-basin. Therefore, we used multiple HRUs for sub-basin analysis in this research.…”
Section: Model Configurationmentioning
confidence: 99%
“…We calibrated a crop yield because calibration using a crop yield gives more confidence on actual evapotranspiration, and hence give the precise estimation of other water components such as, soil moisture, surface runoff and percolation [15]. The SUFI-2 algorithm was used to calibrate the crop parameters and uncertainty analysis.…”
Section: Calibration Based On Crop Yieldmentioning
confidence: 99%
See 1 more Smart Citation